2022
DOI: 10.26434/chemrxiv-2022-lkzbj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoimaging of solid solution domains during phase transitions inside LiNi0.5Mn1.5O4

Abstract: Lithiation dynamics in many battery cathode materials remain poorly understood, because of the difficulty in differentiating inter and intra-particle heterogeneity. In this work, operando X-ray nanodiffraction microscopy is used to directly image the structural evolution inside Li1-xMn1.5Ni0.5O4 single crystals during electrochemical delithiation. Metastable domains of solid-solution intermediates are detected, but are not associated with the reaction front between the lithiated and delithiated phases as predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
4
1
0
Order By: Relevance
“…Figure 6 summarizes the delithiation mechanisms and tilt grain dynamics of the measured particle. The onset of both transition supports the mechanisms proposed in our previous work [12] where we observed different mechanisms for the two phase transitions. The first Li 1 -Li 0.5 phase transition follows a "phase-field" mechanism, growing from multiple points on the surface.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Figure 6 summarizes the delithiation mechanisms and tilt grain dynamics of the measured particle. The onset of both transition supports the mechanisms proposed in our previous work [12] where we observed different mechanisms for the two phase transitions. The first Li 1 -Li 0.5 phase transition follows a "phase-field" mechanism, growing from multiple points on the surface.…”
Section: Discussionsupporting
confidence: 91%
“…The location of these regions also correlates with the most delithiated regions of the crystal (red regions of the strain map in Supplementary Video 1). This also confirms the results of our previous work [12], where we suggested that the regions with sharp tilt boundaries act as nucleation points for the delithiation process due to high concentration of defects.…”
Section: Lattice Tilt Evolution and Intermediate Statesupporting
confidence: 92%
See 3 more Smart Citations